High Performance Liquid Chromatography Recent Advances and Applications - Núñez, Oscar; Sentellas, Sònia; Granados, Mercè; Saurina, Javier (IntechOpen, 2023)
Increasing interest in topics related to health and quality of life in recent years has led to a growing need in food, environmental and bioanalytical research for high-throughput separation techniques able to cope with the qualitative/quantitative determination of a large number of compounds in very complex matrices. High-performance liquid chromatography (HPLC) is a well-established separation technique widely employed in many fields. The versatility of chromatographic separation modes, coupled with low-resolution and high-resolution mass spectrometry, makes HPLC among the best options to solve emerging analytical problems. This book provides an overview of new advances in high-performance liquid chromatography and its applications in different fields.